2014
DOI: 10.1007/s00415-014-7541-2
|View full text |Cite
|
Sign up to set email alerts
|

Tissue microstructural changes in dementia with Lewy bodies revealed by quantitative MRI

Abstract: We aimed to characterize dementia with Lewy bodies (DLB) by the quantitative MRI parameters of longitudinal relaxation time (qT1) and transverse relaxation time (qT2). These parameters reflect potential pathological changes in tissue microstructures, which may be detectable noninvasively in brain areas without evident atrophy, so may have potential value in revealing the early neuropathological changes in DLB. We conducted a cross-sectional study of subjects with DLB (N = 35) and similarly aged control partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…In addition to our previous findings on qMRI changes in DLB [7], as well as the established literature on animal qMRI correlates, the current data provided convergent evidence for the potential ability of quantitative MRI in detecting early changes of tissue property caused by neurodegenerative disease. Being able to apply this novel technique in human using relatively safe MRI method enables new means for early detection of AD and tracking its progression over time.…”
Section: Individual Analysis In Longitudinal Comparisonsupporting
confidence: 81%
See 2 more Smart Citations
“…In addition to our previous findings on qMRI changes in DLB [7], as well as the established literature on animal qMRI correlates, the current data provided convergent evidence for the potential ability of quantitative MRI in detecting early changes of tissue property caused by neurodegenerative disease. Being able to apply this novel technique in human using relatively safe MRI method enables new means for early detection of AD and tracking its progression over time.…”
Section: Individual Analysis In Longitudinal Comparisonsupporting
confidence: 81%
“…In our previous cross-sectional study on dementia with Lewy bodies (DLB), we also found a significant reduction of qMRI parameters in DLB compared to controls [7]. In addition, we showed that the spatial pattern of qMRI alteration only partly overlapped with that of atrophy, making the latter an unlikely explanation for the qMRI decreases.…”
Section: Individual Analysis In Longitudinal Comparisonsupporting
confidence: 56%
See 1 more Smart Citation
“…In previous work by the same authors, decreased T 1 values were found in patients with dementia with Lewy bodies compared with control subjects, highlighting the potential of T 1 measures in general to detect changes caused by neurodegeneration [21]. Using 5xFAD transgenic mice, a well-recognised AD mouse model [2224], we have previously shown that at the age of 11 months, 5xFAD mice have reduced MRI T 1 relaxation times in the lower layers of the posterior parietal and primary somatosensory areas of the cortex and the corpus callosum compared with age-matched wild-type controls [25].…”
Section: Introductionmentioning
confidence: 93%
“…Differences in MTL atrophy between AD and healthy controls measured using semi-quantitative techniques on MRI has shown sensitivity and specificity greater than 85% [56,57,58]. Significant alterations in tissue microstructure measured by longitudinal and transversal relaxation times was found in patients with DLB compared to healthy controls [59]. Differences between AD and other dementias could not be found with similar sensitivity and specificity though [60,61,62].…”
Section: Mri In Dementiamentioning
confidence: 99%